Evaluation of enzyme inhibitors in drug discovery : a guide for m edicinal chemists and pharmacologists - Copeland, Robert Allen (Hoboken, N.J. : Wiley, 2013)
"There has been explosive growth in the hunt for new pharmaceuticall y agents globally. Traditionally, this has been the purview of the pha rmaceutical industry, but today, this effort crosses academic, governme nt, and industry laboratories across the world. Enzymes remain the mos t valued and common of drug targets; hence, a detailed understanding of their interactions with inhibitors is critical to successful drug disc overy. This book provides a practical, readable, and comprehensive trea tment of these topics that allows scientists to master the art of appl ied enzymology for drug discovery. The book addresses the opportunities for inhibitor interactions with enzyme targets arising from considerat ion of the catalytic reaction mechanism; discusses how inhibitors are p roperly evaluated for potency, selectivity, and mode of action, covers the potential advantages and liabilities of specific inhibition modalit ies with respect to efficacy in vivo, and provides valuable biochemical insights to help medicinal chemists and pharmacologists most effective ly pursue lead optimization. It includes two new chapters, one on the pioneering idea of drug-target residence time fostered by Dr. Copeland, and the second on quantitative biochemistry. Five new appendices are a dded"--Provided by publisher.
Machine generated contents note: Foreword.Preface.Acknowledgments.1. Why Enzymes as Drug Targets?1.1 Enzymes Are Essentials for Life.1.2 En zyme Structure and Catalysis.1.3 Permutations of Enzyme Structure Durin g Catalysis.1.4 Other Reasons for Studying Enzymes.1.5 Summary.Referenc es.2. Enzyme Reaction Mechanisms.2.1 Initial Binding of Substrate.2.2 N oncovalent Forces in Reversible Ligand Binding to Enzymes.2.2.1 Electro static Forces.2.2.2 Hydrogen Bonds.2.2.3 Hydrophobic Forces.2.2.4 van d er Waals Forces.2.3 Transformations of the Bond Substrate.2.3.1 Strateg ies for Transition State Stabilization.2.3.2 Enzyme Active Sites Are Mo st Complementary to the Transition State Structure.2.4 Steady State Ana lysis of Enzyme Kinetics.2.4.1 Factors Affecting the Steady State Kinet ic Constants.2.5 Graphical Determination of kcat and KM2.6 Reactions In volving Multiple Substates.2.6.1 Bisubstrate Reaction Mechanisms.2.7 Su mmary.References.3. Reversible Modes of Inhibitor Interactions with Enz ymes.3.1 Enzyme-Inhibitor Binding Equilibria.3.2 Competitive Inhibition .3.3 Noncompetitive Inhibition.3.3.1 Mutual Exclusively Studies.3.4 Unc ompetitive Inhibition.3.5 Inhibition Modality in Bisubstrate Reactions. 3.6 Value of Knowing Inhibitor Modality.3.6.1 Quantitative Comparisons of Inhibitor Affinity.3.6.2 Relating Ki to Binding Energy.3.6.3 Definin g Target Selectivity by Ki Values.3.6.4 Potential Advantages and Disadv antages of Different Inhibition Modalities In Vivo.3.6.5 Knowing Inhibi tion Modality Is Important for Structure-Based Lead Organization.3.7 Su mmary.References.4. Assay Considerations for Compound Library Screening .4.1 Defining Inhibition Signal Robustness, and Hit Criteria.4.2 Measur ing Initial Velocity.4.2.1 End-Point and Kinetic Readouts.4.2.2 Effects of Enzyme Concentration.4.3 Balanced Assay Conditions.4.3.1 Balancing Conditions for Multisubstrate Reactions.4.4 Order of Reagent Addition.4 .5 Use of Natural Substrates and Enzymes.4.6 Coupled Enzyme Assays.4.7 Hit Validation and Progression.4.8 Summary.References.5. Lead Optimizat ion and Structure-Activity Relationships for Reversible Inhibitors.5.1 Concentration-Response Plots and IC50 Determination.5.1.1 The Hill Coef ficient.5.1.2 Graphing and Reporting Concentration-Response Data.5.2 Te sting for Reversibility.5.3 Determining Reversible Inhibition Modality and Dissociation Constant.5.4 Comparing Relative Affinity.5.4.1 Compoun d Selectivity.5.5 Associating Cellular Effects with Target Enzyme Inhib ition.5.5.1 Cellular Phenotype Should Be Consistent with Genetic Knocko ut or Knockdown of the Target Enzyme.5.5.2 Cellular Activity Should Req uire a Certain Affinity for the target Enzyme.5.5.3 Buildup of Substrat e and/or Diminution of Product for the Target Enzyme Should Be Observed in Cells.5.5.4 Cellular Phenotype Should Be Reversed by Cell-Permeable Product or Downstream Metabolites of the Target Enzyme Activity.5.5.5 Mutation of the Target Enzyme Should Lead to Resistance or Hypersensiti vity to Inhibitors.5.6 Summary.References.6. Slow Binding Inhibitors.6. 1 Determining kobs: The Rate Constant for Onset of Inhibition.6.2 Mecha nisms of Slow Binding Inhibition.6.3 Determination of Mechanism and Ass essment of True Affinity.6.3.1 Potential Clinical Advantages of Slow Of f-rate Inhibitors.6.4 Determining Inhibition Modality for Slow Binding Inhibitors.6.5 SAR for Slow Binding Inhibitors.6.6 Some Examples of Pha rmacologically Interesting Slow Binding Inhibitors.6.6.1 Examples of Sc heme B: Inhibitors of Zinc Peptidases and Proteases.6.6.2 Example of Sc heme C: Inhibition of Dihydrofolate Reductase by Methotresate.6.6.3 Exa mple of Scheme C: Inhibition of Calcineurin by FKBP-Inhibitor Complexes .6.6.4 Example of Scheme C When Ki* << Ki: Aspartyl Protease Inhibitors .6.6.5 Example of Scheme C When k6 Is Very Small: Selective COX2 Inhibi tors.6.7 Summary.References.7. Tight Binding Inhibitors.7.1 Effects of Tight Binding Inhibition Concentration-Response Data.7.2 The IC50 Value Depends on Kiapp and [E]T.7.3 Morrison's Quadratic Equation for Fiting Concentration-Response Data for Tight Binding Inhibitors.7.3.1 Optimiz ing Conditions for Kiapp Determination Using Morrison's Equation.7.3.2 Limits on Kiapp Determinations.7.3.3 Use of a Cubic Equation When Both Substrate and Inhibitor Are Tight Binding.7.4 Determining Modality for Tight Binding Enzyme Inhibitors.7.5 Tight Binding Inhibitors Often Disp lay Slow Binding Behavior.7.6 Practical Approaches to Overcoming the Ti ght Binding Limit in Determine Ki.7.7 Enzyme-Reaction Intermediate Anal ogues as Example of Tight Binding Inhibitors.7.7.1 Bisubstrate Analogue s.7.7.2 Testing for Transition State Mimicry.7.8 Potential Clinical Adv antages of Tight Binding Inhibitors.7.9 Determination of [E]T Using Tig ht Binding Inhibitors.7.10 Summary.References.8. Irreversible Enzyme In activators.8.1 Kinetic Evaluation of Irreversible Enzyme Inactivators.8 .2 Affinity Labels.8.2.1 Quiescent Affinity Labels.8.2.2 Potential Liab ilities of Affinity Labels as Drugs.8.3 Mechanism-Based Inactivators.8. 3.1 Distinguishing Features of Mechanism-Based Inactivation.8.3.2 Deter mination of the Partition Ratio.8.3.3 Potential Clinical Advantages of Mechanism-Based Inactivators.8.3.4 Examples of Mechanism-Based Inactiva tors as Drugs.8.4 Use of Affinity Labels as Mechanistic Tools.8.5 Summa ry.References.Appendix 1. Kinetic of Biochemical Reactions.A1.1 The Law of Mass Action and Reaction Order.A1.2 First-Order Reaction Kinetics.A 1.3 Second-Order Reaction Kinetics.A1.4 Pseudo-First-Order Reaction Con ditions.A1.5 Approach to Equilibrium: An Example of the Kinetics of Rev ersible Reactions.References.Appendix 2. Derivation of the Enzyme-Ligan d Binding Isotherm Equation.References.Appendix 3. Serial Dilution Sche mes.Index.
Includes bibliographical references and index.
Keywords: Enzyme Inhibitors -- therapeutic use; Drug Design; Enzyme Inhibitors -- chemistry